GERAK NIAGA MALUKU-PAPUA ZONA EKONOMI DAN KEKUASAAN ISLAM - Wuri Handoko (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2010)
Moluccas and of Papua, geographically bunch up and have potency of good natural resource. In Region Moluccas, standing centers power of Islam which consist of Ternate, Tidore, Bacan and Jailolo (Moluko Kie Raha). History note, extension of power of Islam from one of the empire of that Islam till to region of Papua. Archaeological data also prove the existence of influence of Islam in region of Papua. Extension of Moluccan Islam to Papua, representing the effort which braid to braid with activity of trading. Of Moluccas region till to Papua, woke up by economic zona to strengthen and formation of trade network, at the same time as effort maintain and widen power of Islam.